Experimenta l investigation of tribological characteristics of nanocrystalline nickel protective coating developed through electro deposition technique. (2016) - Venkatesh, C.; Karthi, A.S.; Logeswaran, T.; Prithivirajan, V.; Santhosh, M.
Abstract: The moving parts of any mechanism and machine parts are always subjected to a significant wear due to the development of friction. It is utmost important aspect to address the wear problems in present environment. But the complexity goes on increasing to replace the worn out parts if they are very precision. Technology advancement in surface engineering ensures the minimum surface wear with the introduction of polycrystalline nano nickel coating. In this study, tribological behavior of the nano nickel coating developed through pulsed electro deposition technique has been investigated. The nano structured coated specimen were admitted for pin and disc method of wear testing. The nature of wear has been examined over the surface of the specimen through Atomic Force Microscope (AFM) in order to validate the prior results. The results yielded from pin and disc and AFM registered the negligible deviations.